Identification of Risk Factors Characteristics of Transfusion Reaction - Eko Putri Rahajeng; Raehana Samad; Rachmawati Muhiddin (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2020)
Blood transfusion is an important part of health care. A blood transfusion can be carried out after careful consideration of its risks and benefits. One of the important considerations for blood transfusion is adverse transfusion reaction. Several risk factors for a transfusion reaction are age, gender, repeated transfusion, disease diagnosis, type of blood component, and blood incompatibility. This research is a descriptive study performed at Blood Bank Dr. Wahidin Sudirohusodo Hospital, Makassar, from January to December 2017. The subjects were all patients reported to have an acute transfusion, totaling 104 subjects. The descriptive method was carried out by the calculation of frequency distribution. From January to December 2017, 104 patients with transfusion reactions were obtained, predominantly were male (53.8%), with the lowest age range of ≥ 60 years (27.9%), packed red cell as the most found blood components (82.4%), a history of previous transfusion reactions (72.1%), and a diagnosis of malignancy (53.9%). The history of repeated transfusions is the most common risk factor compared to age, gender, blood component, and patient diagnosis.